Upaya Meningkatkan Hasil Belajar IPA menggunakan Model Picture and Picture dengan Media Animasi di SDS Muhammadiyah Selat Tahun Pelajaran 2016/2017 - Muhamad Faisal Budiono; Aidin Najihi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to improve learning outcomes and describe the learning activities of Va SDS Muhammadiyah Selat students using Animation media. The subjects in this study consisted of 27 students, 14 men, and 13 women. Data collection techniques used were observation and tests. Data analysis uses qualitative and quantitative data analysis. The results of this study indicate that the use of animation media can improve the learning outcomes of science students in VA class SDS Muhammadiyah Straits of Kuala Kapuas. This is based on the results of research with the acquisition of values in the learning activities that have been carried out for two cycles, it can be concluded that: The use of poster media can improve student learning outcomes, this can be seen from the pre-action average = 40.55 with classical completeness 7.40 %, the average cycle I = 45 with classical completeness 22.27% and cycle II = 72 with classical completeness 88.88%.